Tujuan Pendidikan Nasional Perspektif Al-Qur’an - Rahman Affandi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: The National Education functions to develop skills and form the character and civilization of the nation’s dignity in the context of the intellectual life of the nation, aims to develop students’ potential to become a man who is faithful and devoted to God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and become a democratic and responsible citizen. Meanwhile, the purpose of education according to the Koran is to foster a human, so it can perform its functions as a servant of Allah and His caliphs, in order to build a world in accordance with the established concept of God. In other words, its aim is to nurture students to become complete human beings, so get a good happiness of the world and the hereafter. Key words: Objectives of education, perfect man, and happiness